Hydroponics and aquaponics promoting today's agriculture for tomorrow's food security (The Philippine Journal of Crop Science, 2018)
The Philippines is confronted by a critical decision to make in combatting one of the biggest challenges facing humanity- food security. As the United Nations warned that the world could loss a quarter of global food production by 2050 due to the combined effects of economic, environmental and social factors, the country is presently suffering from the major impacts of climate change such as extreme weather events and water scarcity aggravated by natural and man-made disasters. Regrettably, food production is still at the mercy of nature despite the advances in agriculture, from farm mechanization, water management, protected cultivation and plant genetics. Alarmed by these issues, the government called for urgent rational policies to sustain domestic food production and promote urban farming using climate-smart technologies. In response, the Central Luzon State University (CLSU) promptly embarked on researches related to climate-smart agriculture to formulate suitable adaptation techniques in improving productivity. This is in cognizance of the FAO's optimistic prediction that there will be abundant food supply in the future only if farmers will shift from traditional to high-technology farming systems combined with computerized equipment. In 2000, CLSU started establishing a demonstration farm to promote Israeli technologies on automated drip irrigation for geoponic production of honeydew melon in greenhouses and other crops in the open field. This was followed by the fabrication of indigenous tropical greenhouse and automatic controllers triggered by soil moisture and time for pressurized irrigation and research on soiless culture. With funding support from DOST-PCAARRD, CLSU has established a demonstration farm for hydroponics and aquaponics for different production systems for cucurbits, tomato, pepper, leafy vegetables, herbs, and other aquacultural crops. With working models as proofs of concepts that advanced production techniques can be done using locally available materials and Filipino ingenuity, various stakeholders from rural and urban areas here and abroad are asking technical assistance in constructing their systems. Conduct of seminar-workshops and the use of social media enhance the promotion of the technology.